Three different calculations to compute a swimmer's instantaneous active drag profile and variations in the parameter values that arise as a consequence - Mason, B. R.; Sacilotto, G.; Hazrati, P.; Franco, R. (Biomechanics and Medicine in Swimming 2014, at Canberra, Australia, Volume: XIIth International Symposium in Biomechanics and Medicine in Swimming, 2014)
The Australian Institute of Sport has developed a free swim analysis system called the Assisted Towing Method (ATM) designed to estimate a swimmer`s instantaneous whole body active drag parameter at maximum swim velocity. The computed active drag parameter may then be used to assist in the biomechanical assessment of the swimmer`s free swimming technique. The ATM method involves towing the swimmer at approximately a five percent greater speed than the swimmer`s maximum swim velocity, using a tow which allows a swimmer`s natural intra stroke velocity fluctuations to occur. The swimmer must apply equal maximum power and use similar swimming technique in both the assisted tow and unassisted swim, as well as maintain a mean constant speed throughout both conditions. The varying drag force and varying velocity profiles are used in the computation of active drag. A cubic function obtained from the maximum swim velocity and the tow velocity is used to compute the swimmer`s active drag parameter by multiplying the drag force profile by this cubic function (Mason et al, 2013). In the first calculation, just the mean swim velocities are used in the cubic function. In the second calculation the instantaneous variable velocities are used. In the third calculation a factor incorporating the acceleration profile is applied to the second calculation. METHOD: Four elite male freestyle sprint swimmers were tested using the ATM and their active drag parameters were computed using the three different calculations. Although the ATM equation to calculate the active drag parameter in the first and second calculation uses the same formula, different velocity values for Vassist and Vfree are used in the calculation. Da =Ftow * (Vassist*Vfree**2) In calculation 1 Vassist and Vfre are only mean velocity values. ( Vassist **3 -Vfree**3) In calculation 2 Vassist and Vfre are the instantaneous velocities. In the third calculation, the swimmer`s acceleration profile is included as part of the calculation and this results in a change in the formula for the instantaneous active drag parameter. Calculation of Active Drag Da = ma(Vassist*Vfree**2 -Vfree**3) - (Ftow*Vassist*Vfree**2) ( Vassist **3 - Vfree**3) The formula variables are: Da = active drag parameter values Ftow = drag force profile values as measured by force plate Vassist = tow velocity profile values as measured by dynamometer Vfree = free swim velocity profile values computed from Vassist a = acceleration profile values (derivative of Vassist profile) m = inertia of swimmer (mean passive drag value at max swim velocity) NB. Vfree profile for assisted trials is identical in shape to the Vassist profile but is reduced by a value equal to (Mean of Vassist - Mean of Vfree ). ANALYSIS: The three different active drag parameters for each subject were computed and comparisons between each of the three were performed to identify similarities and differences that occur between the three calculated active drag parameters. RESULTS: Results were consistent over all four subjects. Mean active drag and mean propulsive force values were very similar for all three calculations. There were only very slight variations in the active drag, propulsion and net force parameters using the first two calculations. The third calculation resulted in a much larger range in values for the active drag parameter that became positive in its peaks. This resulted in a consequential reduction in the range of the propulsion parameter. The net force parameter remained essential the same for all three calculations. CONCLUSION: As a consequence of the third calculation producing peaks in the active drag parameter that became positive at the peaks, the researchers would advise only using the first two calculation methods.